Globalization, citizenship & subjectivity in my family: an analysis of the changes in the last four generations - Wagle, Anita (Shaheed Smriti Journal, 2021)
Globalization has been increasingly affecting human subjectivities as well as the notion of citizenship The process of globalization has not left Nepal. This study describe how globalization, especially related to citizenship effect my family subjectivity though which routes over the generation. The first citizenship Act arrived in 2020 BS but the notion of citizenship interred into Kavre with Land Reform Act 2021. Citizenship is security and belongingness for the old generation but it is identity and necessary documents for the young. Panchayat was responsible for creating the feelings of nationalism for grandfather but for the son emerge only special circumstances but for the young generation it is nothing. Regarding the desires, thinking, perception between the people of generation varies in great deal. The present generation involve themselves in the technological activities whereas the first generation seems to take it as “Aakash jamin ko pharak” (great different). Social status is capital for old generation but skill and knowledge is capital for the new generations. On the basis of the theoretical groundings as well as case study, we can conclude that globalization is gradually shaping as well as changing the notion of subjectivity, nation-state and citizenship and performing the role of Meta field.